Income Tax Law Reconstruction in Addressing E-Commerce Abuse as the Transaction Proceeds of Crime - Santoso, Didit; Yudha Pramana (Digital Economy and Digital Transformation Review, 2023)
The exponential growth of Indonesia's e-commerce sector—projected to reach US$95 billion by 2025—presents both economic opportunities and regulatory challenges. This study explores the legal nexus between digital income generation and tax compliance, emphasizing the vulnerabilities of e-commerce platforms to various forms of financial fraud and income tax avoidance. Utilizing a normative juridical method under an interpretive paradigm, the research analyzes prevailing income tax laws and their limitations in addressing digital-era fraud, including identity theft, phishing, cybercrime, and misuse of digital financial services. The study identifies the insufficiency of existing legal instruments—particularly secondary rules—in fully capturing the scope of digital transactions and proposes a legal reconstruction of income tax laws. Drawing on H.L.A. Hart’s theory of law as a system of primary and secondary rules, the analysis highlights critical gaps in rule of recognition, rule of change, and rule of adjudication within current Indonesian tax law frameworks. The study concludes by recommending doctrinal reform to reinforce legal clarity, regulatory enforcement, and transnational coordination in the taxation of digital economic activities.